The yellowhorn AGL transcription factor gene XsAGL22 contributes to ABA biosynthesis and drought tolerance in poplar. (2nd November 2021) - Bian, Zhan; Wang, Xiaoling; Lu, Junkun; Wang, Dongli; Zhou, Yangyan; Liu, Yunshan; Wang, Shengkun; Yu, Zequn; Xu, Daping; Meng, Sen
Abstract: Regulation of abscisic acid (ABA) biosynthesis helps plants adapt to drought stress, but the underlying molecular mechanisms are largely unclear. Here, a drought-induced transcription factor XsAGL22 was isolated from yellowhorn ( Xanthoceras sorbifolium Bunge). Yeast one-hybrid and electrophoretic mobility shift assays indicated that XsAGL22 can physically bind to the promoters of the ABA biosynthesis-related genes XsNCED6 and XsBG1, and a dual-luciferase assay showed that XsAGL22 activates the promoters of the later two genes. Transient overexpression of XsAGL22 in yellowhorn leaves also increased the expression of XsNCED6 and XsBG1 and increased cellular ABA levels. Finally, heterologous overexpression of XsAGL22 in poplar increased ABA content, reduced stomatal aperture and increased drought resistance. Our results suggest that XsAGL22 is a powerful regulator of ABA biosynthesis and plays a critical role in drought resistance in plants.